The right to bilingual and intercultural education from a plurilegal perspective in Peru (Società e diritti, 2018)
The author outlines the character of the law of multi-lingual education in Peru in the light of the paradigms of legal pluralism and of interlegality, outlining an effective reconstruction of the characteristics of the juridical system in a genuinely multicultural country.Key words: legal pluralism, multicultural country, education